Enterprise Architecture Planning Using TOGAF Framework Case Study Dampit Village - Delinda Dyta Puspitasari; Made Kamisutara (NAROTAMA UNIVERSITY, 2021)
As an administrative area under the Sub-District, Kelurahan Dampit does not yet have an information system and information technology that supports its activities, such as technical administration for all activities inside Kelurahan Dampit, reporting and monitoring of monitoring of community activities, administration of correspondence, population registration, inventory of problems related to community services, manufacturing report on the implementation of duties and filing. Therefore, it is necessary to plan an enterprise architecture to increase the effectiveness of work in public services, reporting, monitoring and managing the internal functions of the Kelurahan. This study discusses the planning of enterprise architecture in Kelurahan Dampit using the TOGAF (The Open Group Architecture Framework) framework with the ADM (Architecture Development Method) method as a method used for guidance or tools to plan, design, develop and implement information system architecture. This enterprise architecture planning will produce a business architecture blueprint that describes business processes, an application architecture that describes application design and interactions with other related applications, a data architecture that describes data storage, management and access, a technology architecture that describes the supporting hardware and software application infrastructure as well as the roadmap for implementing the application for Kelurahan Dampit.